2017
DOI: 10.5152/tjbh.2017.312017
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm Shift From Halstedian Radical Mastectomy to Personalized Medicine

Abstract: The paradigm shift in breast cancer biology has changed the management of breast cancer from radical mastectomy to precision medicine. In the late 19 th century, William Steward Halsted thought that breast cancer was a local-regional disease, and he proposed radical mastectomy, which became the standard surgical treatment of breast cancer for nearly 100 years (1). Halsted succeeded in decreasing the locoregional recurrence rate to 6% at 5 years in contrast to his European counterparts, whose local recurrence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Both Halstedian and Fisherian hypotheses recommend certain treatment protocol to all patients with breast cancer. Along with “the spectrum theory” as reviewed by Özmen, 87 we should separate low-risk patients from high-risk patients to avoid overtreatment for low-risk patients. It is likely that certain percentage of low-risk patients accompanying good prognostic factors do not require systemic and/or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Both Halstedian and Fisherian hypotheses recommend certain treatment protocol to all patients with breast cancer. Along with “the spectrum theory” as reviewed by Özmen, 87 we should separate low-risk patients from high-risk patients to avoid overtreatment for low-risk patients. It is likely that certain percentage of low-risk patients accompanying good prognostic factors do not require systemic and/or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular features of distant metastasis remain largely unknown, and it is still impossible to accurately predict it in breast cancer. Breast cancer is considered a systemic disease at the onset as a consequence of cells entering lymphatics or veins, and it is suggested that distant metastasis is not a random event, but is, at least in a part, determined by characteristics of breast carcinoma cells at the primary site. Therefore, in this study, we first examined the gene expression profile of ER‐positive stage IV breast carcinoma tissues based on microarray analysis, and newly identified OLFM4 , LY6D and S100A7 as genes closely linked to distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Halsted proposed that breast cancer spread from the breast to the pectoralis muscle then to regional lymph nodes and then finally to distant sites (1). Based on this very plausible theory, clinicians adopted an aggressive surgical approach to achieve local control.…”
Section: Breast Cancer Theories and Evolution Of Bcsmentioning
confidence: 99%
“…One hundred years ago, during the Halstedian era, women with breast cancer were treated with surgery alone, radical mastectomy and axillary clearance regardless of the stage at presentation (1). From this 'one size fits all' approach, we have progressed to tailored and personalized management, taking into consideration individual patient and tumour factors.…”
Section: Introductionmentioning
confidence: 99%